The Influence of Work Motivation, Work Facilities, and Compensation on Job Satisfaction - Marthen Ragowino Bira; Puspita Wulansari; Maria Apsari Sugiat (International Journal of Indonesian Business Review, 2026)
This study aims to identify Work Motivation, Work Facilities, and Compensation of Pokdarwis Members of Prai Ijing Traditional Village, and to identify how Work Motivation, Work Facilities, and Compensation contribute to job satisfaction partially and simultaneously. The method used is descriptive analysis through descriptive analysis techniques and multiple regression with SPSS 26 analysis tools. The sample used is a Saturated Sample with Non-Probability Sampling Technique to 500 Members of Pokdarwis Prai Ijing Traditional Village. The preliminary research results suggest that Work Motivation, Work Facilities, and Compensation are in the good range, and that Work Motivation, Work Facilities, and Compensation contribute partially and simultaneously. The conclusion in this study is that Work Motivation has an effect on Job Satisfaction. Work Facilities have an effect on Job Satisfaction. Compensation has an effect on Job Satisfaction and Work Motivation, Work Facilities, and Compensation have an effect simultaneously on Job Satisfaction of Pokdarwis Kampung Adat Prai Ijing.